Agricultural schools and agroecology. Meanings, appropriations and co-production of knowledge - Martínez, Darío Gabriel (Millcayac - Revista Digital de Ciencias Sociales, 2025)
This article investigates the contributions of agricultural schools to the agroecological transition. The objective was to observe the characteristics of this issue based on fieldwork carried out in two educational institutions within the horticultural belt of the city of La Plata (Argentina). The tensions between agroecology and conventional vegetable production are evident in curriculum designs from different periods, in teaching practices, and in the interventions of school agents. These questions led us to inquire about the ways in which students applied their knowledge at home or in family production units.